A cephalometric analysis of the cranial base and frontal part of the face in patients with mandibular prognathism - Čutović, Tatjana; Jović, Nebojša; Stojanović, Ljiljana; Radojičić, Julija; Mladenović§, Irena; Matijević, Stevo; Kozomara, Ružica (Vojnosanitetski pregled, 2014)
Bacground/Aim. The literature suggests different views on the correlation between the cranial base morphology and size and saggital intermaxillary relationships. The aim of this study was to investigate the cranial base morphology, including the frontal facial part in patients with mandibular prognathism, to clarify a certain ambiguities, in opposing viewspoints in the literature. Methods. Cephalometric radiographies of 60 patients were analyzed at the Dental Clinic of the Military Medical Academy, Belgrade, Serbia. All the patients were male, aged 18–35 years, with no previous orthodontic treatment. On the basis of dental and sceletal relations of jaws and teeth, the patients were divided into two groups: the group P (patients with mandibular prognathism) and the group E (the control group or eugnathic patients). A total of 15 cephalometric parametres related to the cranial base, frontal part of the face and sagittal intermaxillary relationships were measured and analyzed. Results. The results show that cranial base dimensions and the angle do not play a significant role in the development of mandibular prognathism. Interrelationship analysis indicated a statistically significant negative correlation between the cranial base angle (NSAr) and the angles of maxillary (SNA) and mandibular (SNB) prognathism, as well as a positive correlation between the angle of inclination of the ramus to the cranial base (GoArNS) and the angle of sagittal intermaxillary relationships (ANB). Sella turcica dimensions, its width and depth, as well as the nasal bone length were significantly increased in the patients with mandibular prognathism, while the other analyzed frontal part dimensions of the face were not changed by the malocclusion in comparison with the eugnathic patients. Conclusion. This study shows that the impact of the cranial base and the frontal part of the face on the development of profile in patients with mandibular prognathism is much smaller, but certainly more complex, so that morphogenetic tests of the maxillomandibular complex should be included in further assessment of this impact.